ANALISIS SEMIOTIK REPRESENTASI MASKULINITAS PADA IKLAN BCA “DON’T KNOW? KASIH NO!” - Ridwan Omaryanto, Osama (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
The aim of this research is to find out how the representation of masculinity is constructed in the BCA advertisement